2008
DOI: 10.1111/j.1462-5822.2008.01149.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of the attachment of Kaposi's sarcoma-associated herpesvirus (KSHV)-infected human B cells to extracellular matrix by KSHV-encoded gB and cellular αV integrins

Abstract: SummaryKaposi's sarcoma-associated herpesvirus (KSHV) has two modes of replications: latent and lytic replications. Reactivation from latency is dictated, in part, by the cell cycle. Herein, we have attempted to delineate the importance of cell cycle in KSHV pathogenesis by exploring the expression pattern of cellsurface receptors during different phases of the cell cycle. aV integrin expression is augmented during S phase in fibroblasts, epithelial and KSHV-infected cells. Using a Matrigel system, we pioneer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The gB-and gL-positive cells were sorted using a flow cytometer based on the expression of GFP. The time at which the mixture of cells was seeded onto 12-well plates was considered as 0 h. At different time points (1,4,8,12,24,48,72,96, and 120 h) post-seeding, the cells were lysed, RNA was extracted, cDNA was prepared, and the expression of ORF50 was monitored by qRT-PCR using specific primers. The relative copy numbers of the ORF50 transcripts were calculated from the standard graph plotted using the Ct values for different dilutions of in vitro transcribed ORF50 (using ORF50/pGEM-T plasmid).…”
Section: Kshv Infection Of Hmvec-d Cells-hmvec-d Cells Were Infected mentioning
confidence: 99%
See 1 more Smart Citation
“…The gB-and gL-positive cells were sorted using a flow cytometer based on the expression of GFP. The time at which the mixture of cells was seeded onto 12-well plates was considered as 0 h. At different time points (1,4,8,12,24,48,72,96, and 120 h) post-seeding, the cells were lysed, RNA was extracted, cDNA was prepared, and the expression of ORF50 was monitored by qRT-PCR using specific primers. The relative copy numbers of the ORF50 transcripts were calculated from the standard graph plotted using the Ct values for different dilutions of in vitro transcribed ORF50 (using ORF50/pGEM-T plasmid).…”
Section: Kshv Infection Of Hmvec-d Cells-hmvec-d Cells Were Infected mentioning
confidence: 99%
“…A previous study conducted by our laboratory demonstrated that KSHV-infected cells supporting a lytic infection directed adhesion of cells. The mechanism of cell-cell adhesion, specifically in cells supporting a late stage of lytic replication, was mediated by gB instead of cellular integrins (8). This led us to suggest that gB expressed on the cell membranes may have a significant role in KS pathogenesis, particularly inducing cell survival signaling in cells apart from its role in virus binding, entry, and egress (7,9,10).…”
mentioning
confidence: 99%
“…Envelope glycoprotein gB interacts with a variety of cell surface molecules including heparan sulfate and integrins to facilitate virus binding and entry [9, 17]. There is growing evidence that demonstrates significant roles of gB interactions to modulate a variety of cell signaling pathways to induce a cellular state that is receptive for virus replication [13, 14, 23, 37]. In a recent study, we demonstrated cell membrane-associated gB to promote adhesion over migration of infected cells via RGD motif [13].…”
Section: Discussionmentioning
confidence: 99%
“…Both RGD and DLD are well-characterized integrin-binding domains with an important role in KSHV-cell interactions critical to mediating virus entry into cells [9-11]. Using soluble gB [12] and membrane-associated gB [13, 14], it was demonstrated that the RGD motif in KSHV gB can mediate adhesion of cells. Recent work from our laboratory using recombinant gB proteins lacking both the RGD and DLD domains demonstrated the following: (i) independently, RGD interactions mediate attachment of cells while DLD interactions regulate migration of cells; (ii) however, when both RGD and DLD are placed juxtaposed in the same protein, like in gB, the RGD interaction-induced attachment of cells overshadows the ability of DLD-mediated signaling to induce migration of cells [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation